Pemberdayaan Kelompok Nelayan Berbasis Potensi Lokal Melalui Fish Smoking Technology Di Sendang Biru, Kabupaten Malang, Jawa Timur - Defrian Marza Arisandi; Guntur Guntur; Supriyadi Supriyadi; Mentari Puspa Wardani; Attabik Mukhammad Amrillah; Burhan Fauzi Salam (Journal of Innovation and Applied Technology, 2021)
The main problems exist in fishing communities were the low level of education, marine knowledge, capital ownership and fisheries business management. The purpose of this technology product disseminated to the Community is to create added value for fishery products through the manufacture of smoked fish, provide good business and financial management skills, provide facilitation for improving the quality of smoked fish product packaging. The justification of proposer and partners in solving priority scale problems is carried out in a concrete manner through the following implementation methods: 1) preparation; 2) application of fish smoking technology; 3) training; 4) monitoring and evaluation.